Molecular Investigation of Plasmid–Mediated Quinolone Resistant Genes among aminoglycoside-resistant uropathogenic Escherichia coli Isolates from Babylon Hospitals, Iraq - Khadeeja Obaid Alm’amoori1, Zainab Jaber Hadi2, Ali Muhsin Almohana3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Uropathogenic E coli is the most frequently causes of UTIs in humans ,accountable 75- 95 % of UTIs. PMQR have been identified in family Enterobacteriaceae worldwide. The purpose of this study to examine the dissemination of aac(6’)-Ib-cr and PMQR genes in isolates of UPEC.Method : A cross sectional study of mid-stream urine of the participate patients their approval for direction usage their specimen. The susceptibility test by disk diffusion for UPEC were isolated from urine and screening of quinolone resistant by multiplex PCR for qnrA, qnrB and qnrS genes and monoplex PCR for qunD ,qepA and aac(6’)-Ib-cr genes.Results : A total of 1072 mid-stream urine were collected randomly, overall 132 were identified E. coli , among these 60 aminoglycoside resistant UPEC isolates were screened to the five quinolone antibiotics. The resistance proportion to nalidixic acid and ciprofloxacin were 75.0%, as well as to lomefloxacin, norfloxacin and levofloxacin were 76.7%, 73.3% and 71.7%, respectively. The susceptibility test for antibiotics showed a high incidence of the resistance to the majority of antibiotics class. It was found that 73.3%, 38.3% , and 20.0% of the isolates harbored aac(6’)-Ib-cr, qnrS and qnrB genes ,respectively either alone or in combination, while the qnrA. qunD ,qepA genes were not detected.Conclusion : All isolates were identified as multiple antibiotic resistances, only one isolate can be considered as possible PDR and high prevalence of aac(6’)-Ib-cr, qnrS and qnrB genes among isolates.